Body and politics : elite disability sport in China - Zhixun, Guan; Hong, Fan (Sports and athletics preparation, performance, and psychology, 2017)
"This book focuses on elite disability sport in China in the context of history, politics, policies and practice from 1979 to 2012. It examines the relationship between athletes with disabilities and the three major disability games: the Paralympic Games, the Special Olympic Games and the Deaflympic Games. Three key questions are asked: What policies have ensured the success of elite disability sport? How do the elite sport system and management of elite disability sport work in China? In what way has elite disability sport empowered athletes with disabilities in China? The book includes a comprehensive literature review on the historical development of disability sport in China and beyond. Functionalism and empowerment are the major theoretical backgrounds for the research. The former analyses the function of elite sport policies, systems and other factors occurring during the process, whilst the latter examines the relationship of empowerment between elite disability sport and athletes in China. The three major disability competitions are used as case studies. The book concludes by indicating some potential future directions for further research"--